On the question of determining the cost of paintwork of wheeled vehicles with elements of airbrushing - Mykhalskyi, Oleh; Kiriakov, S.; Fokin, Denis (Archives of Criminology and Forensic Sciences, 2020)
This article outlines problematic issues in determining the cost of paintwork of wheeled vehicles with elements of airbrushing. Options of applying patterns on the auto parts of the body depending on their complexity and the possibility of reapplication are considered. Ways of calculating the number of man-hours on airbrushing work are taken out, namely tabular data on already existing methodological recommendations as well as alternative, more accurate ways of calculating standard time are suggested, which at most reflect real costs, both for the time spent on airbrushing drawing, and on the amount of materials accordingly.